Pertanggungjawaban Perusahaan Asuransi Terhadap Pemegang Polis Yang Mengalami Status Polis Lapse (Kehilangan) Akibat Kelalaian Agen Dalam Pembayaran Angsuran Premi (Studi Kasus Putusan No.320/Pdt.G/2019/Pn Mdn) - Riska Fitriani Siregar; M.Citra Ramadhan; Marsella Marsella (JUNCTO: Jurnal Ilmiah Hukum, 2023)
The existence of an agreement is a condition that must be met for the validity of an agreement. The agreement regulates the rights and obligations, the importance of insurance in its development to advance the development of insurance. Paying the premium is not on time, so that the insurance claim submitted is rejected by the company, because it is already in a state of Lapse. Failure to pay is not the insured's fault, but the agent's fault for not paying the premium to the company. This study aims to find out how agents are regulated in insurance companies in Indonesia and how insurance companies are responsible for customers who experience policy lapse due to agent negligence in paying premiums. Normative juridical research methods. The nature of the research is analytical descriptive with a literature study approach (Library Research) and field studies at the Medan District Court (Case Study of Decision No.320/Pdt.G/2019/Pn Mdn). The results of the study explained that the defendant (PT. Prudential Life Assurance) was completely irresponsible and there was no good faith towards the plaintiff (yurnawilis) who claimed the insurance of the deceased insured. Ambun Sari (the plaintiff's biological mother), the case was also stated as obscuur libel (fuzzy) posita and the plaintiff's petitum were not related, it does not mean that the defendant was not responsible for insurance claims.